2015
DOI: 10.1371/journal.pone.0140510
|View full text |Cite
|
Sign up to set email alerts
|

Lower Incidence of End-Stage Renal Disease but Suboptimal Pre-Dialysis Renal Care in Schizophrenia: A 14-Year Nationwide Cohort Study

Abstract: Schizophrenia is closely associated with cardiovascular risk factors which are consequently attributable to the development of chronic kidney disease and end-stage renal disease (ESRD). However, no study has been conducted to examine ESRD-related epidemiology and quality of care before starting dialysis for patients with schizophrenia. By using nationwide health insurance databases, we identified 54,361 ESRD-free patients with schizophrenia and their age-/gender-matched subjects without schizophrenia for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…In the United States, it has been found that patients with schizophrenia have a higher mortality rate than the general population not only due to unnatural deaths such as suicide, homicide, and accidents but also due to natural deaths [31]. In Taiwan, it has been found that these patients are more likely to die from physical illnesses such as myocardial infarction [32], strokes [33], diabetic mellitus [34], renal disease [35], and cancer [36]. Patients with schizophrenia in Taiwan have shorter lives than the general population when they have comorbid physical illnesses [31,37].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, it has been found that patients with schizophrenia have a higher mortality rate than the general population not only due to unnatural deaths such as suicide, homicide, and accidents but also due to natural deaths [31]. In Taiwan, it has been found that these patients are more likely to die from physical illnesses such as myocardial infarction [32], strokes [33], diabetic mellitus [34], renal disease [35], and cancer [36]. Patients with schizophrenia in Taiwan have shorter lives than the general population when they have comorbid physical illnesses [31,37].…”
Section: Discussionmentioning
confidence: 99%
“…There are other reports that the prevalence of CKD is not different between schizophrenic patients and control [4], and the incidence of end-stage renal disease is low in schizophrenic patients [42]. Rej S [43] and Kessing LV [44] showed that Li, mood stabilizing treatment for bipolar disorder, had an effect on renal function and induced CKD.…”
Section: Discussionmentioning
confidence: 96%
“…Tzeng et al [ 42 ] reported that schizophrenia is associated with a 25% increase in the risk of developing CKD for 3 years follow up period. There are other reports that the prevalence of CKD is not different between schizophrenic patients and control [ 4 ], and the incidence of end-stage renal disease is low in schizophrenic patients [ 43 ]. Rej [ 44 ] and Kessing [ 45 ] showed that Lithium, mood stabilizing treatment for bipolar disorder, had an effect on renal function and induced CKD.…”
Section: Discussionmentioning
confidence: 99%